ZigBee-based communication system for data transfer within future microgrids - Setiawan, M.; Shahnia, Farhad; Rajakaruna, Sumedha; Ghosh, Arindam (The Institute of Electrical and Electronics Engineers, Inc, 2015)
A wireless data communication system for future microgrids (MGs) is presented in this paper. It is assumed that each MG has a central controller and each distributed generation unit in the MG has a local controller. The communication system is responsible for transmitting and receiving data amongst these controllers. This communication system is based on ZigBee technology, which is a low cost and low power consumption device. However, its main limitation is the low data transfer rate. To reduce the number of data transactions, a data management scheme is presented in this paper. The required data to be transferred are defined and a suitable coding is proposed. Finally, the number of transmitted symbols and the processing time of the proposed data management scheme are numerically analyzed. In addition, the dynamic operation of an MG is evaluated considering the delays that are imposed by this communication system.